Anestesia untuk Operasi Syringomyelia C2-7 dengan Penyulit Obesitsas Mellitus Tipe II - Betty Roosiati; Bambang J. Oetoro (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2012)
Syringomyelia refers to the cystic cavitation of the spinal cord. Two main forms of syringomyelia have been described: communicating syringomyelia and non communicating syringomyelia. In communicating syringomyelia, there is primary dilatation of the central canal that is often associated with abnormalities at the foramen magnum such as tonsillar herniation (Chiari malformation) and basal arachnoiditis. In non communicating syringomyelia, a cyst arieses within the cord substance itself and does not communicate with the central canal or subarachnoid space. This patients is clasified as communicating syringomyelia due to Chiari malformation. Obesity and diabetes mellitus type II as comorbid in this case. The surgery was done under general anesthesia, prone position uneventfull.Anethesia for C2-7 Syringomyelia Surgery with Comorbid Obesity and Diabetes Mellitus Type IISyringomyelia adalah kista pada medulla spinalis. Ada dua bentuk utama dari syringomyelia yaitu communicating syringomyelia dan non communicating syringomyelia. Communicating syringomyelia adalah dilatasi primer dari kanalis sentralis dan sering berhubungan dengan abnormalitas pada foramen magnum, misal herniasi tonsillar (Chiari Malformasi) dan arachnoiditis basal. Non communicating syringomyelia, kista berasal dari medulla spinalis dan tidak berhubungan dengan kanalis sentralis atau ruang subarachnoid. Pasien ini termasuk golongan communicating syringomyelia karena adanya Chiari malformasi. Obesitas dan diabetes mellitus tipe II sebagai comorbid. Operasi dilakukan dengan anestesi umum dalam posisi prone.